Insulin hypersensitivity in type 1 diabetes: investigation and treatment with immunodepletion. (19th April 2020) - Harvey, John N; Cronin, Michael; Arkwright, Peter
Abstract: A 12‐year‐old girl presented with type 1 diabetes which was well controlled for the first two years. Glycaemic control then markedly deteriorated with a very large increase in insulin requirement and the appearance of inflammatory nodules at injection sites. Immunoprecipitation studies showed this to be due to a type 3 hypersensitivity reaction with the generation of IgG autoantibodies binding to insulin itself. Trials of a wide range of different insulins and treatment with a hyposensitisation protocol provided no benefit. Following treatment with rituximab, antibody generation subsided. Since the clinical response was only partial she also received intravenous immunoglobulin. A reduced insulin requirement and better glycaemic control were achieved over time. These parameters have subsequently deteriorated again. Copyright © 2020 John Wiley & Sons.